Morphological features of histogenic differon cells in connective tissue of guinea pigs’ lungs after sensitization with ovalbumin - S. S. Popko; V. M. Yevtushenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
An urgent issue of modern morphology is establishing a number of patterns of morphological changes and reactivity of connective tissue components of lungs in case of experimental sensitization with allergens.